Summarize of Electric Vehicle Electric System Fault and Fault-tolerant Technology - Zhang Liwei; Huang Xianjin; Yang Yannan; Xu Chen; Liu Jie (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Electric vehicle drive system is a multi-variable function, running environment complexed and changeable system, so it’s failure form is complicated. In this paper, according to the fault happens in different position, establish vehicle fault table, analyze the consequences of failure may cause and the causes of failure. Combined with hardware limitations, and the maximum guarantee system performance requirements, passive software redundancy fault-tolerant strategy is put forward, give an example to analysis the pros and cons of this method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4410